Studies on acacia gums: Part VII effect of exudates form and tree age on the characteristics of Acacia seyal var. seyal and Acacia seyal var. fistula. (March 2015) - Andres-Brull, Marina; Abdalla, Ishragha G.; Cirre, Jesus; Edwards, James; Osman, Mohammed E.; Phillips, Glyn O.; Al-Assaf, Saphwan
Abstract: Authenticated samples of Acacia seyal var. seyal and Acacia seyal var. fistula have been investigated. Samples of each variety from young (5–7 years) and old trees (15–20 years) were collected during the same season from the Eldamazeen area of Sudan. For each variety, two types of gum exudates (seep and nodule form) were collected. The solubility, optical rotation, sugar composition, colour Gardner, viscosity, and molecular weights were measured. The rhamnose and uronic acid contents were higher in var. seyal than var. fistula but the amount of arabinose is greatest in var. fistula . The galactose content is almost the same for all samples with the possible exception of var. seyal with a higher content in older trees. The weight average molecular weight (Mw ) for var. fistula is almost double that of var. seyal and generally the proportion of the high molecular fraction increases with age. The average value for the Mw of the arabinogalactan moiety (AG) is 6.2 × 10 5 and 9.3 × 10 5  g/mol for seyal and fistula respectively. Tannin content is highest in seep (∼0.8 wt%), lowest in the nodule form (0.08 wt%) and is a contaminant resulting directly from contact of the gum exudate with the tree bark. Tannin content increases with the age of tree for seyal var. seyal but not for var. fistula samples. These results give a clear difference between these two Acacia gum varieties, both of which are currently regulatory approved as gum arabic for food use. Graphical abstract: Highlights: Acacia seyal var. seyal and var. fistula samples of different shape and tree age collected from the same region and season. Rhamnose and uronic acid contents are higher in var. seyal than var. fistula while arabinose is greatest in var. fistula . Tannin content in both depends on the gum exudates contact with the bark. Higher molecular weight and viscosity in var. fistula compared to var. seyal .